2009
DOI: 10.1016/j.pbb.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the antinociception caused by ethanolic extract obtained from the leaves of Melissa officinalis (lemon balm) in mice

Abstract: The present study examined the antinociceptive effect of the ethanolic extract from Melissa officinalis L. and of the rosmarinic acid in chemical behavioral models of nociception and investigates some of the mechanisms underlying this effect. The extract (3-1000 mg/kg), given orally (p.o.) 1 h prior to testing, produced dose-dependent inhibition of acetic acid-induced visceral pain, with ID50 value of 241.9 mg/kg. In the formalin test, the extract (30-1000 mg/kg, p.o.) also caused significant inhibition of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 45 publications
1
51
0
1
Order By: Relevance
“…A previously published study has reported that the antinociceptive effects of Melissa officialis ethanolic extract in formalin and glutamate induced pain behaviors may be related to rosmarinic acid as a major phenol constituent of the plant. Moreover, oral administration of RA can produce a significant inhibition of the nociceptive response caused by intraplantar injection of glutamate into the mouse hind paw which is in accordance with the observed anti-nociceptive effect of RA (10 mg/kg) in the healthy rats (Guginski et al, 2009). Furthermore, according to a recent paper, RA at the doses used in this study, induced anti-nociception by inhibiting acetic acid induced abdominal constriction in mice (Lucarini et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A previously published study has reported that the antinociceptive effects of Melissa officialis ethanolic extract in formalin and glutamate induced pain behaviors may be related to rosmarinic acid as a major phenol constituent of the plant. Moreover, oral administration of RA can produce a significant inhibition of the nociceptive response caused by intraplantar injection of glutamate into the mouse hind paw which is in accordance with the observed anti-nociceptive effect of RA (10 mg/kg) in the healthy rats (Guginski et al, 2009). Furthermore, according to a recent paper, RA at the doses used in this study, induced anti-nociception by inhibiting acetic acid induced abdominal constriction in mice (Lucarini et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Rosmarinic acid (RA) (Shetty, 2005). It has been reported that RA has diverse biological properties, such as antioxidant (Moon et al, 2010), antiinflammatory (Chu et al, 2012), analgesic (Guginski et al, 2009;Lucarini et al, 2013), anticancer (Moon et al, 2010), and neuroprotective (Ono et al, 2012) activity.…”
Section: Introductionmentioning
confidence: 99%
“…), oxide nitric synthase substrate. Doses and drug administration schedules were selected based on previous reports and on pilot experiments in our laboratory (Pinardi et al, 2003;Vale et al, 2007;Bezerra et al, 2008;Guginski et al, 2009) and were administered 30 min before Urtica circularis extract (100 mg/kg, i.p.) The nociceptive response was evaluated in the acetic acid-induced abdominal writhing test.…”
Section: Acetic Acid-induced Abdominal Writhingmentioning
confidence: 99%
“…In this study, the strongest antibacterial activity was manifested by the ethanol extract. Earlier works showed that the ethanol extract of M. officinalis can possess an antioxidant (Yanishlieva and Marinova, 2006) and antinociceptive effect (Guginski et al, 2009).…”
Section: Discussionmentioning
confidence: 99%